Xantogranulomatous Salpingo Oophritis, Lessons Learnt: Report of Two Cases With Unusual Presentation - Ruchi Rathore; Shivangi Chauhan; Suman Mendiratta; Ritu Sharma; Manupriya Nain; Namrata Sarin (Journal of Family and Reproductive Health, 2018)
Xanthogranulomatous inflammation is a rare form of chronic inflammatory response consisting of macrophages, lymphocytes, plasma cells and neutrophils too. Due to its locally destructive nature and mass forming capacity as a result of adhesions, this type of inflammation may mimic  malignancy or tuberculosis both clinically and radiologically. We present a report of two such cases, one mimicking tuberculosis and the other mimicking malignancy clinically. Awareness of this condition and a higher index of suspicion among clinicians, radiologists and pathologists can help in early diagnosis and more appropriate treatment of this potentially destructive disorder.